Thermodynamics and dielectric properties of the NH₄H₂PO₄ type antiferroelectrics - Levitskii, R.R.; Lisnii, B.M.; Baran, O.R. (Condensed Matter Physics, 2002)
Within the framework of the proton model we study thermodynamic and
static dielectric properties of the ADP type antiferroelectrics with taking into
account the tunnelling effects of protons on hydrogen bonds. In the fourparticle
cluster approximation for the short-range interactions and in the
mean field approximation for the long-range interactions we calculate the
free energy, entropy, and components of static dielectric susceptibility of the
crystals. We also get the system of equations for the sublattice proton order
parameter and an equation for the phase transition temperature. We find
the values of the theory parameters for the NH₄H₂PO₄ and NH₄H₂AsO₄
crystals and get a good agreement between the theoretical results and the
corresponding experimental data for the temperature dependences of the
spontaneous sublattice polarization, proton specific heat, longitudinal and
transverse static dielectric permittivities of the crystals. В рамках протонної моделі досліджуються термодинамічні та статичні діелектричні властивості антисегнетоелектричних кристалів типу ADP з врахуванням ефектів тунелювання протонів на водневих зв’язках. В наближенні чотиричастинкового кластера по короткосяжних і молекулярного поля по далекосяжних взаємодіях розраховано вільну енергію, ентропію, компоненти тензора статичної діелектричної сприйнятливості, отримано систему рівнянь для параметра протонного впорядкування підгратки та рівняння для температури фазового переходу. Знайдено значення параметрів теорії для кристалів NH₄H₂PO₄ та NH₄H₂ASO₄ і отримано добре узгодження результатів теоретичного розрахунку з відповідними експериментальними даними для температурних залежностей спонтанної поляризації підгратки, протонної теплоємності, поздовжньої і поперечної статичних діелектричних проникностей цих кристалів.